Determination of Emergency Conditions: How Government Fulfill the Workers Rights during Large-scale Social Restrictions? - Elsa Mellinda Saputri (The Indonesian Journal of International Clinical Legal Education, 2020)
Some of regions in Indonesia decided to implement Large-Scale Social Restrictions to reduce the spread and transmission of the corona virus. Large-Scale Social Restrictions are restrictions on certain activities to people in a certain area who are suspected of being infected with the corona virus to prevent the possibility of spreading and spreading. The Indonesian Ministry of Health has issued regulations regarding the technical implementation of Large-Scale Social Restrictions through Minister of Health Regulation No. 9 of 2020 concerning Large-Scale Social Limitation Guidelines in the Framework of Accelerating Handling of Corona Virus Disease 19 (Covid-19). Large-Scale Social Restrictions will have an impact on the reduction or cessation of worker's activities and the income or rights of workers that may be reduced or even not given by the company. For companies that continue to operate normally when implementing Large-Scale Social Restrictions, in order to provide security procedures and ensure work safety for their workers. Whereas companies that terminate employment must fulfill their workers' rights and implement government programs as skills development support programs such as the Pre-Employment Card, improve social protection programs through exemptions from cutting electricity payments, family hope programs, and basic needs. Finally, Indonesian President Joko Widodo issued three legal products in accordance with the mandate of Law Number 6 of 2018 on Health Quarantine. But from the perspective of Constitutional Law in a State of Emergency, the three legal products cause problems.